2018
DOI: 10.3174/ajnr.a5620
|View full text |Cite
|
Sign up to set email alerts
|

Edge Contrast of the FLAIR Hyperintense Region Predicts Survival in Patients with High-Grade Gliomas following Treatment with Bevacizumab

Abstract: Background and Purpose Treatment with bevacizumab is standard of care for recurrent high grade gliomas (HGGs); However, monitoring response to treatment following bevacizumab remains a challenge. The purpose of this study is to determine whether quantifying the sharpness of the fluid-attenuated inversion recovery (FLAIR) hyperintense border using a measure derived from texture analysis—edge contrast (EC)—improves the evaluation of response to bevacizumab in patients with HGG. Materials and Methods MRIs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A 3D analysis was applied to the FLAIR VOI to enhance the local precision and decrease the partial volume effect [40][41][42][43]. The technique of EC extraction has been described in our previous study [44], where the morphological operations of erosion and dilation were applied to the FLAIR VOL binary mask using a spherical 3D mask. Then, the contour of the FLAIR VOL binary mask was drawn in 3D indexing the surface of the FLAIR VOL lesion.…”
Section: Border Distinctnessmentioning
confidence: 99%
“…A 3D analysis was applied to the FLAIR VOI to enhance the local precision and decrease the partial volume effect [40][41][42][43]. The technique of EC extraction has been described in our previous study [44], where the morphological operations of erosion and dilation were applied to the FLAIR VOL binary mask using a spherical 3D mask. Then, the contour of the FLAIR VOL binary mask was drawn in 3D indexing the surface of the FLAIR VOL lesion.…”
Section: Border Distinctnessmentioning
confidence: 99%
“…In addition, T2 FLAIR is increasingly involved in the texture analysis for assessment of therapeutic response and survival outcomes. It has been reported that 3D shape features could distinguish pseudoprogression from true progression and lower edge contrast of the FLAIR signal is correlated with poor survival after bevacizumab treatment [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 93 radiomic features, including shape, first order features, and second-order features (Supplementary Table 2 ), were extracted from the mask. In addition, edge contrast calculation was performed, that characterizes the tumor border, as previously described (Supplementary Information S1 ) 60 . The final set consisted of 263 radiomic features (14 shape features + 83 first-order and second-order 14 features × 3 sequences) for each patient.…”
Section: Methodsmentioning
confidence: 99%